PREVENTION OF ACCIDENT INCIDENTS IN GAS SUPPLY SYSTEMS AND IMPROVING PERFORMANCE - Aytbayev , K.R; Qurbaniyazov, A.J (Innovative Development in Educational Activities, 2023)
This article provides information on the creation of a system of their design and use and the laying of gas pipelines in determining the strength of gas supply networks.